Numerical analysis of flow around infinite and finite cylinders at trans-critical Reynolds numbers with and without surface roughness - Burger, Abri Andre Spies (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.